Wastewater treatment in constructed wetlands = Oczyszczanie ścieków w oczyszczalni hydrofitowej - Nowak, Agnieszka Joanna; Królik, Dariusz; Kostecki, Jakub (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Constructed wetlands are an alternative and economically reasonable way for the wastewater from dispersed development treatment. Existing systems showed that the effectiveness of this treatment is high. The whole treatment process depends on many factors such as time of operation, type of filling, temperature. Constructed wetlands with proper construction and operation are safe for the environment and users.
Keywords: oczyszczanie ścieków; oczyszczalnia hydrofitowa; ścieki z zabudowań; wastewater treatment; constructed wetlands; wastewater from buildings